Türk-Macar münasebetleri ışığı altında II. Rákóczi Ference ve Macar mültecileri sempozyumu, İstanbul Üniversitesi, Edebiyat Fakültesi, 31 Mayıs-3 Haziran 1976 = Symposium onRákóczi Ferenc II and the Hungarian refugees in the light of Turco-Hungarian cultural relations, University of İstanbul, the Faculty of Lettres, 31 May-3 June 1976 (İstanbul)
239 s.